Experimental Investigation on Greener Self-Compacting Concrete With Inclusion of Rice Husk Ash - Hareindirasarma, S.; Athapaththu, D.; Sivasankaranarayana, S.; Janarthanan, B. (University of Jaffna, 2022)
Self-compacting concrete (SCC) has become more popular than conventional concrete owing to its advantages, such as a high level of consistency, finishability, and flow rate with the least possible water-cement ratio. So far, researchers have conducted their research on self-compacting concrete based on various factors that may affect the compressive strength and fresh properties of SCC. Only a few SCC mix designs consider the impact of minerals such as rice husk ash (RHA), silica dust and fly ash. Therefore, this paper looks forward to assessing the effect of the addition of RHA on the compressive strength of self compacting concrete with various mixing designs. To conduct this research, 5 to 14 mm size aggregates were employed in this research study. After developing seven SCC mixes, cement was partially replaced with locally collected RHA at 5, 10, 15 and 20%, respectively. In addition, data analysis was conducted, and experimental results were carefully monitored using graphical methods and SPSS software by checking the variation of compressive strength against different factors such as RHA percentage, curing period and water-cement ratio. According to the results, a higher strength was encountered with 5% white-ash RHA, which contained more amorphous silica than carbon.
Keywords: Self-compacting concrete; Rise Husk Ash (RHA); Slump flow; Compressive strength; Low-Carbon; High-Carbon